IL-23 inhibitor enhances the effects of PTEN DNA-loaded lipid nanoparticles for metastatic CRPC therapy - Chen, Xinlu; Gong, Luyao; Wang, Yuanyuan; Ye, Chen; Guo, Huanhuan; Gao, Shen; Chen, Jiyuan; Wang, Zhuo; Gao, Yuan (Frontiers in Pharmacology, 2024)
Introduction: Metastatic castration-resistant prostate cancer (mCRPC) patients face challenges due to limited treatment options. About 50% of patients with mCRPC have a functional loss of phosphatase and tensin homology deleted on chromosome 10 (PTEN), leading to tumor progression, metastasis, and immune suppression. Moreover, elevated IL-23 produced by myeloid-derived suppressor cells (MDSCs) is found in CRPC patients, driving tumor progression. Therefore, a combination strategy based on PTEN restoration and IL-23 inhibition may block CRPC progression and metastasis. Methods: The antitumor effect of restoring PTEN expression combined with the IL-23 inhibitor Apilimod was studied in a mouse model of bone metastasis CRPC and mouse prostate cancer RM-1 cells. To verify the targeting ability of PTEN DNA coated with lipid nanoparticles (LNP@PTEN) in vitro and in vivo. In addition, RT-qPCR and flow cytometry were used to investigate the related mechanisms of the antitumor effect of LNP@PTEN combined with Apilimod. Results: LNPs exhibited significant tumor-targeting and tumor accumulation capabilities both in vitro and in vivo, enhancing PTEN expression and therapeutic efficacy. Additionally, the combination of LNP@PTEN with the IL-23 inhibitor Apilimod demonstrated enhanced inhibition of tumor growth, invasion, and metastasis (particularly secondary organ metastasis) compared to other groups, and extended the survival of mice to 41 days, providing a degree of bone protection. These effects may be attributed to the PTEN function restoration combined with IL-23 inhibition, which help reverse immune suppression in the tumor microenvironment by reducing MDSCs recruitment and increasing the CD8+/CD4+ T cell ratio. Discussion: In summary, these findings highlight the potential of LNPs for delivering gene therapeutic agents. And the combination of LNP@PTEN with Apilimod could achieve anti-tumor effects and improve tumor microenvironment. This combinational strategy opens new avenues for the treatment of mCRPC.